Strategi Digital Marketing Untuk Mengatasi Penurunan Harga Olahan Singkong Dan Pisang Di Desa Sidasari - Dias Setianingsih; Muhamad Syafiqul Humam; Laela Nur Azizah; Leonardo Adzan Utama; Rizka Fadhila; Vika Adisty (JRCE (Journal of Research on Community Engagement), 2025)
This research focuses on the problem of price reduction for processed cassava and banana products in Sidasari Village, which is an area with extensive agricultural potential, especially for these two types of commodities. Local micro, small, and medium enterprises (UMKM) face various serious challenges, including increasing levels of competition, lack of innovation in marketing strategies, and limited access to the market, resulting in the erosion of profit margins. To overcome this problem, this study offers and implements digital marketing strategies as a much-needed solution. The approach taken in the methodology is Asset Based Community Development (ABCD), with a focus on the 5D stage which includes Discovery, Dream, Design, Define, and Destiny. This method is oriented towards identifying and mobilizing local assets, such as the availability of abundant raw materials, high entrepreneurial spirit, and access to digital technology, to empower the local community. The training given in digital marketing includes a variety of techniques, including the use of WhatsApp Business, Instagram, TikTok, product photography, and content creation for promotion. The implementation of digital marketing aims to increase product visibility, expand market reach beyond local boundaries, and build a stronger awareness of Sidasari's processed product brands. By utilizing existing digital platforms, this strategy makes it possible to promote more effectively and at a lower cost, while encouraging direct interaction with consumers, which will ultimately lead to increased sales and competitiveness. This initiative is purposed to make Sidasari Village as a center for local food processing, as well as promoting sustainable economic independence and social solidarity in the community.